Neodymium iron boron and preparation method thereof

By loading multi -alloy coating on the free surface of the iron boron porn and laser melting and quenching treatment, combined with hydrogen breaks and sintering and other processes, the problem of fineness and stubbornness of the grain grain and stubborn force of the iron boron magnetic body. Achieve efficient magnetic performance improvement.

CN119381149APending Publication Date: 2025-01-28GANZHOU DMEGC RARE EARTH MAGNET CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310933824.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

It is difficult for the prior art to refine the grains of neodymium iron boron magnets, balance the grain boundary phase components and enhance coercive forces.

Method used

By loading the CO consecutive coating on the free surface of the tin iron boron dumpling tablet and the FE base light rare earth alloy, the pulse laser melting and quenching treatment are performed, combined with hydrogen break, powder, molding, and other static pressure treatment. Finally, sintering and thermal treatment are carried out to prepare the iron boron magnets with high stubbornness.

Benefits of technology

The refinement of the cymbal iron boron magnets, the balance of the composition of the crystal world, and the improvement of the stubborn force, at the same time avoid the needs of adding heavy rare earth and complex processes, and have the advantages of commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004362961330000081
    Figure BDA0004362961330000081
  • Figure BDA0004362961330000091
    Figure BDA0004362961330000091
Patent Text Reader

Abstract

The invention provides neodymium iron boron and a preparation method thereof. The preparation method comprises the following steps: S1, providing first mixed slurry, wherein the first mixed slurry comprises a Co-based alloy, a Fe-based light rare earth alloy and a solvent; mixing the first mixed slurry with a slow release agent to obtain second mixed slurry; s2, enabling the second mixed slurry to form a coating on the free surface of the neodymium iron boron throwing sheet to obtain a semi-finished throwing sheet; s3, pulse melting treatment is conducted on the coating of the semi-finished throwing piece, then quenching treatment is conducted, and a melted throwing piece is obtained; s4, hydrogen demolishing, powder making, forming and isostatic pressing treatment are sequentially conducted on the fused throwing sheet, and a green body is obtained; and then the green body is sintered, and neodymium iron boron is obtained. By means of the preparation method, the problems that in the prior art, refining of neodymium-iron-boron magnet grains, balance of grain boundary phase components and improvement of coercive force are difficult to achieve can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic material preparation, and in particular to neodymium iron boron and a preparation method thereof. Background Art

[0002] NdFeB magnetic materials have been widely used in cutting-edge fields such as wind power, new energy, energy-saving motors, and magnetic levitation due to their excellent magnetic properties. Since the advent of NdFeB materials, with the advancement of production and preparation technology, the material magnetic energy product has basically approached the theoretical value of NdFeB, but the material coercivity is less than 30% of the theoretical value, so how to improve the coercivity of NdFeB has become a technical problem that needs to be overcome in the current technical field.

[0003] The existing technical methods generally include the following: 1. Dual alloy process, through the design of single main phase and multiple auxiliary phases, heavy rare earth with high coercivity is distributed in the grain boundary phase, and light rare earth phase with high magnetic energy product is preferentially distributed in the main phase, optimizing the microstructure and achieving high comprehensive performance; 2. Grain boundary diffusion process, by coating a layer of heavy rare earth compound on the surface of the magnet and then diffusing it at high temperature, the heavy rare earth is evenly distributed in the grain boundary phase to form a heavy rare earth shell, improve the organizational structure, and increase the coercivity; 3. Grain refinement process, making the magnetic domain phase in the grain as close to the single domain as possible, thereby achieving an increase in coercivity.

[0004] The dual alloy process or grain boundary diffusion process can optimize the grain boundaries, but it is difficult to achieve grain refinement. The grain refinement process is limited by the coarse crystal phase structure of the flinging sheet and the principle of airflow mill crushing. If you want to achieve grain refinement, you can only decompose and crush the coarse grains in the flinging sheet, which leads to the lack of grain boundary components in the crushed grains, and it is impossible to form an ideal phase in the subsequent heat treatment process. Moreover, during the high-speed collision and crushing of coarse grains in the airflow mill, the crushing is irregular transgranular fracture, resulting in a large proportion of non-spherical grain models, a large number of coarse and fine grains, and uneven particle size distribution, which further limits the particle size of airflow milling, and the ultimate coercive force of the material is also limited by this.

[0005] Pulse laser melting technology refers to the use of laser heat source, with adjustable spot surface and laser power, to quickly melt and quench the coated alloy layer and the surface of the metal part, forming an ideal alloy structure on the metal surface, effectively improving the physical and chemical properties of the metal.

[0006] For example, patent CN10619185B discloses a method of laser cladding self-fluxing nickel-based alloy powder and nano rare earth hydride powder on the surface of a heat-treated magnet, and then performing grain boundary diffusion. Patent CN109065315A discloses a method of laser cladding antiferromagnetic oxide and heavy rare earth dysprosium terbium alloy powder on the surface of a heat-treated magnet, using the antiferromagnetic oxide exchange sheet effect, and then performing grain boundary diffusion. Patent CN112635188A discloses a method and equipment for laser cladding heavy rare earth wire.

[0007] The above three examples all use laser melting to melt heavy rare earth elements onto the surface of the magnet after heat treatment, and then use the grain boundary diffusion process to evenly distribute the heavy rare earth elements in the grain boundary phase, improve the grain boundary structure, and enhance the coercivity of the magnet. The above three methods all have the disadvantages of poor coercivity enhancement effect, large heavy rare earth loss, and complex process.

[0008] Patent CN103632835A discloses a composite process that combines a rapid-setting belt-spinning process, a magnetic field-assisted laser melting technology, and a thermal deformation process to rapidly prepare NdFeB magnets by layer-by-layer oriented melting and deposition. This method cannot guarantee the uniformity of magnetic properties because layer-by-layer melting cannot guarantee the uniformity of magnetic properties, and multiple auxiliary magnetic fields and laser melting affect the degree of orientation, and the uniformity is not as good as the traditional process.

[0009] In summary, the application of pulsed laser melting technology still has many shortcomings.

[0010] In view of this, it is necessary to provide a method that can overcome the above-mentioned deficiencies, refine the grains, balance the grain boundary phase components, and improve the coercive force of the NdFeB magnet. Summary of the invention

[0011] The main purpose of the present invention is to provide a NdFeB magnet and a preparation method thereof, so as to solve the problem in the prior art that it is difficult to achieve grain refinement, balance grain boundary phase composition and increase coercivity of NdFeB magnets.

[0012] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a preparation method of NdFeB is provided, which comprises: S1, providing a first mixed slurry, the first mixed slurry comprising a Co-based alloy, an Fe-based light rare earth alloy and a solvent; mixing the first mixed slurry with a sustained-release agent to obtain a second mixed slurry; S2, allowing the second mixed slurry to form a coating on the free surface of the NdFeB sheet to obtain a semi-finished sheet; S3, subjecting the coating of the semi-finished sheet to a pulse melting treatment, followed by a quenching treatment to obtain a fused sheet; S4, subjecting the fused sheet to hydrogen rupture, powder making, molding and isostatic pressing in sequence to obtain a green body; and then subjecting the green body to a sintering treatment to obtain NdFeB.

[0013] Furthermore, in the pulse melting treatment, the diameter of the focused light spot is 0.2 to 2.0 mm, the power is 500 to 3000 kW, and the scanning speed is 20 to 50 mm / s; preferably, the pulse melting treatment is carried out under an inert atmosphere; more preferably, the inert atmosphere is argon and / or nitrogen atmosphere.

[0014] Furthermore, the cooling rate in the quenching treatment is 500-1000°C / min; preferably, the quenching treatment is performed using a cooling gun, and the nozzle aperture of the cooling gun is The diameter is 0.1~0.4mm, and the gas flow rate is 0.01~0.3m 3 / s, the cooling speed is 30-60 mm / s; preferably, the cooling gun is filled with an inert gas; more preferably, the inert gas is argon and / or nitrogen.

[0015] Furthermore, in step S2, the second mixed slurry is sprayed by spraying method, and then the second mixed slurry is cured to form a coating; preferably, the weight of the NdFeB sheet increases by 0.5-1% after spraying; more preferably, the curing temperature is 80-120°C, and the time is 10-20min; more preferably, the alloy in the second mixed slurry is in powder form, and the average particle size of the powder is 2.0-10μm.

[0016] Furthermore, the Fe-based light rare earth alloy is Re x Fe 100-x-y B y , wherein 20<x≤50, 0.5≤y≤1.5, Re is selected from one or more of Pr and Nd; preferably, 30<x<45; preferably, the Fe-based light rare earth alloy also includes one or more of Cu and Co, and 0<Cu≤0.5, 0<Co≤0.3.

[0017] Furthermore, the weight ratio of the Co-based alloy to the Fe-based light rare earth alloy is (0.05-0.2):1; preferably, the Co-based alloy is one or more of Co55 alloy and C050 alloy.

[0018] Furthermore, the weight ratio of the Fe-based light rare earth alloy to the solvent is 1:(0.3-0.8); preferably, the solvent is one or more of ethanol, acetone, and polyvinyl butyrate; more preferably, the solvent is ethanol and polyvinyl butyrate.

[0019] Furthermore, the weight ratio of the first mixed slurry to the sustained-release agent is 1:(0.05-0.15); preferably, the sustained-release agent is polyethylene glycol and / or polyvinyl acetate.

[0020] Furthermore, the hydrogen cracking treatment adopts saturated hydrogen absorption, the dehydrogenation temperature is 500-600°C, the dehydrogenation time is 2-6h, and the medium powder is obtained; preferably, the powder making treatment is air flow milling, and an antioxidant is added in an amount of 0.1-2‰ by weight of the medium powder during the powder making process to obtain a powder, and the particle size of the component is SMD=2-3μm; preferably, the antioxidant is one or more of gasoline, tributyl borate, and ether; preferably, the molding magnetic field in the molding process is 1-2T, and the molding pressure is 50~100MPa; preferably, the pressure in the isostatic pressing treatment is 150~300MPa; preferably, the temperature of the sintering treatment is 1000~1100℃, and the time is 3~8h; more preferably, heat treatment is carried out after sintering treatment, and the heat treatment includes a first-stage heat treatment and a second-stage heat treatment carried out in sequence, wherein the temperature of the first-stage heat treatment is 800~900℃, and the time is 1~3h; wherein the temperature of the second-stage heat treatment is 400~600℃, and the time is 2~8h.

[0021] Furthermore, the iron boron sheet is obtained by melting and casting the heavy rare earth-free N40H formula, and has a thickness of 0.2 to 0.4 mm.

[0022] According to another aspect of the present invention, there is provided a neodymium iron boron obtained according to the above preparation method.

[0023] The technical scheme of the present invention is applied to provide a NdFeB and a preparation method thereof. In the smelting and casting process of the existing process, due to the difference in the cooling gradient of the swing sheet, the cooling speed of the roller surface of the swing sheet is fast, and uniform and fine equiaxed crystals can be formed, and the grain boundary phase components are balanced; however, the free surface of the swing sheet has a limited heat conduction speed and a reduced cooling speed, forming irregular coarse grains and lack of grain boundary phases. In view of this phenomenon, the present invention loads a multi-alloy coating on the free surface of the NdFeB swing sheet, and then performs laser melting and quenching treatment to achieve the refinement of the grains on the free surface of the swing sheet. At the same time, the present invention supplements the Fe-based light rare earth and Co-based alloys, balances the grain boundary phase components of the free surface of the swing sheet, so that in the subsequent hydrogen breaking process, the swing sheet can absorb hydrogen and break along the roller surface and the free surface in both directions, and the medium powder after hydrogen breaking is broken evenly, the grain boundary phase is rich, and the NdFeB is prepared by the method of the present invention. In the subsequent air flow grinding, the transcrystalline crushing is reduced, the proportion of coarse powder and fine powder is reduced, the particle size is refined, and the particle size distribution is concentrated. Taking the above factors into consideration, the preparation method of the present invention can provide a NdFeB with fine grains, balanced grain boundary phase and high coercivity. In addition, the present invention has the advantages of no need to add heavy rare earth and simple process flow, which is conducive to commercial application. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0025] In order to solve the problems in the prior art as described above, according to one aspect of the present invention, a method for preparing NdFeB is provided, which comprises: S1, providing a first mixed slurry, the first mixed slurry comprising a Co-based alloy, an Fe-based light rare earth alloy and a solvent; mixing the first mixed slurry with a sustained-release agent to obtain a second mixed slurry; S2, allowing the second mixed slurry to form a coating on the free surface of the NdFeB sheet to obtain a semi-finished sheet; S3, subjecting the coating of the semi-finished sheet to a pulse melting treatment, followed by a quenching treatment to obtain a fused sheet; S4, subjecting the fused sheet to hydrogen rupture, powder making, molding and isostatic pressing in sequence to obtain a green body; and then subjecting the green body to a sintering treatment to obtain NdFeB.

[0026] In the smelting and casting process of the existing process, due to the difference in the cooling gradient of the swing sheet, the cooling speed of the roller surface of the swing sheet is fast, and uniform and fine equiaxed crystals can be formed, and the grain boundary phase components are balanced; however, the free surface of the swing sheet has a limited heat conduction speed and a reduced cooling speed, forming irregular coarse grains and a lack of grain boundary phase. In view of this phenomenon, the present invention realizes the refinement of the grains on the free surface of the swing sheet by loading a multi-alloy coating on the free surface of the NdFeB swing sheet, and then performing laser melting and quenching treatment. At the same time, the present invention supplements the Fe agent light rare earth and Co-based alloy, balances the grain boundary phase components of the free surface of the swing sheet, so that in the subsequent hydrogen breaking process, the swing sheet can be broken by hydrogen absorption along the roller surface and the free surface in both directions, the medium powder after hydrogen breaking is broken evenly, the grain boundary phase is rich, and the NdFeB is prepared by the method of the present invention. In the subsequent air flow grinding, the transcrystalline crushing is reduced, the proportion of coarse powder and fine powder is reduced, the particle size is refined, and the particle size distribution is concentrated. Taking the above factors into consideration, the preparation method of the present invention can provide a NdFeB with fine grains, balanced grain boundary phase and high coercivity. In addition, the present invention has the advantages of no need to add heavy rare earth and simple process flow, which is conducive to commercial application.

[0027] Specifically, the process of combining laser melting and cold quenching enables the coating and the free surface of the spin piece to complete heating and cooling in a relatively short period of time. This faster temperature change rate enables the grains to be fully refined. During this period, the hydrogen and rare earth elements in the Fe-based alloy in the alloy layer are introduced into the grain boundary neodymium-rich phase structure of the free surface of the NdFeB spin piece to balance the grain boundary phase composition.

[0028] It should be noted that the pulse laser melting process of the present invention processes the free surface of the NdFeB sheet containing a multi-alloy coating. If such a coating structure is not pre-constructed and pulse laser melting is directly performed, the same effect of grain refinement, optimization of grain boundary phase balance and improvement of coercivity as this method cannot be achieved. Similarly, the pulse laser melting process should not be advanced or delayed, otherwise the effect of the technical solution of the present invention cannot be achieved.

[0029] In actual operation, for example, the preparation method of the first mixed slurry can be: Co-based alloy, Fe-based light rare earth alloy, and solvent are mixed, and then added into a planetary ball mill for grinding. Thereafter, an exemplary preparation method of the second mixed slurry can be: the first mixed slurry is mixed with a sustained-release agent, and stirred for 20 minutes; depending on the uniformity of the mixture, the stirring time can vary from 10 to 20 minutes.

[0030] In order to better obtain NdFeB with good physical and chemical structure and thus higher coercivity, in a preferred embodiment, in the pulse melting process, the diameter of the focused light spot is 0.2-2.0 mm, the power is 500-3000 kW, and the scanning speed is 20-50 mm / s; preferably, the pulse melting process is carried out under an inert atmosphere; more preferably, the inert atmosphere is argon and / or nitrogen atmosphere. By regulating the light spot surface and the power of the laser, the melting speed of the alloy coating and the free surface of the NdFeB fling sheet can be controlled, thereby adjusting the physical and chemical properties of the alloy structure reconstruction. The above-mentioned pulse melting parameters also refer to the physical properties of the NdFeB fling sheet, which is more suitable for the fling sheet, a processing object with a thinner thickness. In addition, the inert gas can better protect the melting process.

[0031] In a preferred embodiment, the cooling rate in the quenching treatment is 500-1000°C / min; preferably, the quenching treatment is performed using a cooling gun, and the nozzle aperture of the cooling gun is The diameter is 0.1~0.4mm, and the gas flow rate is 0.01~0.3m 3 / s, cooling speed is 30-60mm / s; preferably, the cooling gun is filled with inert gas; more preferably, the inert gas is argon and / or nitrogen. According to the above conditions, quenching can better achieve rapid cooling of the sheet, thereby better avoiding the problem of coarse grains caused by slow cooling speed in conventional processes, and better improving the coercive force of NdFeB. In actual operation, the terminal temperature of cooling can be 30-200℃.

[0032] In order to make the coating more uniform, in a preferred embodiment, in step S2, the second mixed slurry is sprayed by spraying, and then the second mixed slurry is solidified to form a coating; preferably, after spraying, the weight of the NdFeB sheet increases by 0.5-1%; more preferably, the curing temperature is 80-120°C, and the time is 10-20min; more preferably, the alloy in the second mixed slurry is powdered, and the average particle size of the powder is 2.0-10μm. Through the above preferred parameters, technicians can reasonably control the uniformity of the coating distribution and the thickness of the coating, which is beneficial to the subsequent laser melting and quenching process, and prepare NdFeB with better performance.

[0033] In a preferred embodiment, the Fe-based light rare earth alloy is Re x Fe 100-x-y B y , wherein 0<x≤50, 0.5≤y≤1.5, Re is selected from one or more of Pr and Nd; preferably, 30<x<45; preferably, the Fe-based light rare earth alloy also includes one or more of Cu and Co, and 0<Cu≤0.5, 0<Co≤0.3. The amount of Re added is preferably 30-45, not too much or too little. If it is too much, the light rare earth element will enter the main crystal phase during the melting and quenching process, destroying the magnet design composition and affecting the magnetic properties; if it is too little, it will not be conducive to fully playing the role of regulating the grain boundary phase balance. The content of Fe is also a key parameter that technicians should pay attention to. If the content of Fe is too much, the crystal phase composition cannot be fully and effectively regulated, and the grain refinement effect is poor; on the contrary, if the content of Fe is too little, it will destroy the magnet design composition to a certain extent, thereby affecting the magnetic properties. Among the light rare earths, Pr and Nd are more suitable as the light rare earth components of Fe-based light rare earths because they have better saturation magnetic polarization intensity and anisotropic field, and have cost advantages compared to other heavy rare earth elements. Introducing a small amount of Cu and Co elements into Fe-based light rare earths is more conducive to improving the fluidity of Fe-based light rare earth alloys and adjusting the grain boundary phase composition.

[0034] Unless otherwise specified, in the structural formula of the Fe-based light rare earth alloy of the present invention, the relative ratio of the subscripts of the elements is the ratio of their molar numbers.

[0035] In a preferred embodiment, the weight ratio of the Co-based alloy to the Fe-based light rare earth alloy is (0.05-0.1):1; preferably, the Co-based alloy is one or more of Co55 alloy and C050 alloy. By optimizing the above weight ratio, the composition of the alloy layer can be better regulated, so that it can better play the role of adjusting the grain boundary phase balance, refining the grains, and improving the coercive force.

[0036] In order to make the second mixed slurry better attached to the free surface of the swing sheet, in a preferred embodiment, the weight ratio of the Fe-based light rare earth alloy to the solvent is 1: (0.3-0.8); the preferred solvent is one or more of ethanol, acetone, and polyvinyl butyrate; more preferably, the solvent is ethanol and polyvinyl butyrate. According to the above preferred parameters, the solid content can be better adjusted, and it can be better loaded on the free surface of the swing sheet, which is convenient for subsequent process treatment. When ethanol and polyvinyl butyrate are used in combination, the effect is better.

[0037] In order to make the physical state of the slurry containing the multi-alloy powder more stable, in a preferred embodiment, the weight ratio of the first mixed slurry to the sustained-release agent is 1:(0.05-0.15); preferably, the sustained-release agent is polyethylene glycol and / or polyvinyl acetate. Adding the preferred sustained-release agent according to the above ratio is more conducive to the physical stability of the slurry and facilitates subsequent operations.

[0038] In a preferred embodiment, the hydrogen cracking treatment adopts saturated hydrogen absorption, the dehydrogenation temperature is 500-600°C, the dehydrogenation time is 2-6h, and the medium powder is obtained; preferably, the powder making treatment is air flow milling, and an antioxidant is added in an amount of 0.1-2‰ by weight percentage of the medium powder during the powder making process to obtain a powder, and the particle size of the component is SMD=2-3μm; preferably, the antioxidant is one or more of gasoline, tributyl borate, and ether; preferably, the forming magnetic field in the forming process is 1-2T, and the forming The molding pressure is 50-100MPa; preferably, the pressure in the isostatic pressing treatment is 150-300MPa; preferably, the temperature of the sintering treatment is 1000-1100°C, and the time is 3-8h; more preferably, heat treatment is performed after the sintering treatment, and the heat treatment includes a first-order heat treatment and a second-order heat treatment performed in sequence, wherein the temperature of the first-order heat treatment is 800-900°C, and the time is 1-3h; wherein the temperature of the second-order heat treatment is 400-600°C, and the time is 2-8h. The above-mentioned process conditions are more suitable for the sintering and flinging of the present invention. Due to the beneficial effects provided by the pre-process of the present invention, hydrogen cracking, powder making, molding, isostatic pressing, sintering and heat treatment can better play their effects to obtain a NdFeB magnet with high coercivity.

[0039] In a preferred embodiment, the NdFeB sheet is obtained by melting and casting a heavy rare earth-free N40H formula, and has a thickness of 0.2 to 0.4 mm.

[0040] According to another aspect of the present invention, there is provided a NdFeB magnet prepared by the above-mentioned preparation method. The NdFeB magnet of the present invention has small crystal phase size, balanced grain boundary phase composition and high coercivity.

[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0042] Example 1

[0043] Co-based alloy, Fe-based light rare earth alloy and solvent are mixed in a certain proportion and added into a planetary ball mill for grinding; wherein the Co-based alloy is Co55 alloy powder, the Fe-based light rare earth alloy is Nd 40 Cu 0.5 Co 0.2 B1Fe 余; The solvent is alcohol; the composition ratio is Co-based alloy: Fe-based light rare earth alloy: solvent = 0.1:1:0.6;

[0044] The first mixed slurry and the sustained-release agent are mixed and stirred for 15 minutes, the sustained-release agent is polyethylene glycol, and the composition ratio is the first mixed slurry: sustained-release agent = 1:0.1; in the second mixed slurry, the average particle size of the powder is 2.0-10 μm;

[0045] Use a nitrogen spray gun to spray the spray slurry on the free surface of the N40H material swing sheet, spray weight gain 0.8%, send it into an oven after spraying, bake it at 80°C for 15 minutes to solidify the coating, and obtain a semi-finished swing sheet; wherein the thickness of the swing sheet is 0.2-0.4mm;

[0046] The free surface of the semi-finished sheet was melted by pulse laser in an argon chamber, with a focus spot of 2mm, a power of 1000kW, and a scanning speed of 40mm / s;

[0047] Use an argon cooling gun to quench the free surface of the sheet and cool the nozzle aperture. Air flow 0.05m 3 / s, cooling gun moving speed 50mm / s;

[0048] The obtained fused flakes were hydrogen crushed, and saturated hydrogen absorption was adopted, the dehydrogenation temperature was 560°C, and the dehydrogenation time was 5h to obtain medium powder;

[0049] The medium powder is subjected to air flow grinding, and 0.1% antioxidant is added to control the particle size SMD=2.5 μm; the antioxidant is a mixed solvent of gasoline and tributyl borate;

[0050] The powder is molded and isostatically pressed, the molding magnetic field is 1.8T, the molding pressure is 20MPa, and the green body of 50×40×35mm is pressed, and the isostatic pressing pressure is 230MPa;

[0051] The green body was sintered and heat treated at a sintering temperature of 1100°C for 5 h, a heat treatment temperature of 900°C for 3 h in the first stage, and a heat treatment temperature of 510°C for 6 h in the second stage.

[0052] Example 2

[0053] The difference from Example 1 is that the composition of the Fe-based light rare earth alloy is Pr 10 Nd 30 Cu 0.5 Co 0.2 B1Fe 余 .

[0054] Example 3

[0055] The difference from Example 1 is that the composition of the Fe-based light rare earth alloy is Pr 40 Cu0.5 Co 0.2 B1Fe 余 .

[0056] Example 4

[0057] The difference from Example 1 is that the composition of the Fe-based light rare earth alloy is Nd 20 Cu 0.5 Co 0.2 B1Fe 余 .

[0058] Example 5

[0059] The difference from Example 1 is that the composition of the Fe-based light rare earth alloy is Nd 40 B1Fe 余 .

[0060] Example 6

[0061] The difference from Example 1 is that the composition of the Fe-based light rare earth alloy is Nd 40 Cu1Co 0.5 B1Fe 余 .

[0062] Example 7

[0063] The difference from Example 1 is that the ratio of Co-based alloy:Fe-based light rare earth alloy:solvent=0.05:1:0.3.

[0064] Example 8

[0065] The difference from Example 1 is that the ratio of Co-based alloy:Fe-based light rare earth alloy:solvent=0.1:1:0.8.

[0066] Example 9

[0067] The difference from Example 1 is that the solvent is a mixture of ethanol and polyvinyl butyrate.

[0068] Example 10

[0069] The difference from Example 1 is that the ratio of first mixed slurry: sustained-release agent = 1:0.05.

[0070] Embodiment 11

[0071] The difference from Example 1 is that during pulse laser melting, the focused spot is 0.2 mm, the power is 500 kW, and the scanning speed is 20 mm / s.

[0072] Example 12

[0073] The difference from Example 1 is that during pulse laser melting, the focused spot is 2 mm, the power is 3000 kW, and the scanning speed is 50 mm / s.

[0074] Embodiment 13

[0075] The difference from Example 1 is that during quenching, the cooling gun nozzle The diameter is 0.1mm and the gas flow rate is 0.01m 3 / s, cooling speed is 30mm / s.

[0076] Embodiment 14

[0077] The difference from Example 1 is that during quenching, the cooling gun nozzle The diameter is 0.4mm and the gas flow rate is 0.3m 3 / s, cooling speed is 60mm / s.

[0078] Comparative Example 1

[0079] The difference from Example 1 is that no Fe-based light rare earth alloy is added.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that no Co-based alloy is added. The rest of the process is the same as that of Example 1.

[0082] Comparative Example 3

[0083] The difference from Example 1 is that after pulse melting, the sheets are allowed to cool naturally to room temperature.

[0084] Comparative Example 4

[0085] The difference from Example 1 is that no sustained-release agent is used.

[0086] Comparative Example 5

[0087] The difference from Example 1 is that the pulse melting is adjusted before the coating is sprayed. After the coating is sprayed, subsequent processes such as hydrogen crushing are performed. The rest of the process flow is the same as that of Example 1.

[0088] The magnetic powders obtained in Examples 1 to 14 and Comparative Examples 1 to 5 were tested for particle size using a laser particle size analyzer, and the magnetic properties and crystal phase analysis of the heat-treated magnet blanks were performed using NIM-62000TB and a scanning electron microscope. The results are shown in Table 1.

[0089] Table 1

[0090]

[0091]

[0092] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0093] Through the above embodiments, it is found that by spraying Co-based alloy and Fe-based light rare earth alloy on the free surface of the fling sheet, performing laser melting and rapid quenching treatment, and then preparing magnetic powder of the same particle size by air flow grinding, the powder particle size distribution D90 / D10 is reduced, the distribution is more concentrated, and the grain size of the magnet after sintering heat treatment is effectively reduced, thereby achieving an effective improvement in the coercive force of the magnet without adding heavy rare earth elements.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing neodymium iron boron, characterized in that: include: S1, providing a first mixed slurry, wherein the first mixed slurry comprises a Co-based alloy, a Fe-based light rare earth alloy and a solvent; Mixing the first mixed slurry with a sustained-release agent to obtain a second mixed slurry; S2, allowing the second mixed slurry to form a coating on the free surface of the NdFeB sheet to obtain a semi-finished sheet; S3, performing pulse melting treatment on the coating of the semi-finished sheet, and then performing quenching treatment to obtain a fused sheet; S4, subjecting the fused sheets to hydrogen cracking, powder making, molding, and isostatic pressing in sequence to obtain green compacts; and then subjecting the green compacts to sintering to obtain the NdFeB.

2. The method for preparing NdFeB according to claim 1, characterized in that: In the pulse melting process, the diameter of the focused light spot is 0.2-2.0 mm, the power is 500-3000 kW, and the scanning speed is 20-50 mm / s; preferably, the pulse melting process is carried out under an inert atmosphere; more preferably, the inert atmosphere is argon and / or nitrogen atmosphere.

3. The method for preparing NdFeB according to claim 1 or 2, characterized in that: The cooling rate in the quenching treatment is 500-1000°C / min. Preferably, the quenching treatment is performed using a cooling gun, the nozzle aperture of the cooling gun being The diameter is 0.1~0.4mm, and the gas flow rate is 0.01~0.3m 3 / s, the cooling speed is 30-60 mm / s; preferably, the cooling gun is filled with an inert gas; more preferably, the inert gas is argon and / or nitrogen.

4. The method for preparing NdFeB according to any one of claims 1 to 3, characterized in that: In the step S2, the second mixed slurry is sprayed by a spraying method, and then the second mixed slurry is cured to form a coating; preferably, after the spraying, the weight of the NdFeB sheet increases by 0.5-1%; more preferably, the curing temperature is 80-120°C, and the time is 10-20 minutes; more preferably, the alloy in the second mixed slurry is in powder form, and the average particle size of the powder is 2.0-10μm.

5. The method for preparing NdFeB according to any one of claims 1 to 4, characterized in that: The Fe-based light rare earth alloy is Re x Fe 100-x-y B y , wherein 20<x≤50, 0.5≤y≤1.5, Re is selected from one or more of Pr and Nd; Preferably, 30<x<45; preferably, the Fe-based light rare earth alloy further includes one or more of Cu and Co, and 0<Cu≤0.5, 0<Co≤0.

3.

6. The method for preparing NdFeB according to any one of claims 1 to 5, characterized in that: The weight ratio of the Co-based alloy to the Fe-based light rare earth alloy is (0.05-0.2):1; preferably, the Co-based alloy is one or more of Co55 alloy and C050 alloy.

7. The method for preparing NdFeB according to any one of claims 1 to 6, characterized in that: The weight ratio of the Fe-based light rare earth alloy to the solvent is 1:(0.3-0.8); preferably, the solvent is one or more of ethanol, acetone, and polyvinyl butyrate; more preferably, the solvent is ethanol and polyvinyl butyrate.

8. The method for preparing NdFeB according to any one of claims 1 to 7, characterized in that: The weight ratio of the first mixed slurry to the sustained-release agent is 1:(0.05-0.15); preferably, the sustained-release agent is polyethylene glycol and / or polyvinyl acetate.

9. The method for preparing NdFeB according to any one of claims 1 to 8, characterized in that: The hydrogen cracking treatment adopts saturated hydrogen absorption, the dehydrogenation temperature is 500-600°C, and the dehydrogenation time is 2-6h to obtain medium powder; Preferably, the powder making process is airflow milling, and in the powder making process, an antioxidant is added in an amount of 0.1-2‰ by weight of the medium powder to obtain a powder, and the particle size of the component is SMD=2-3μm; preferably, the antioxidant is one or more of gasoline, tributyl borate, and ether; Preferably, the molding magnetic field in the molding process is 1 to 2 T, and the molding pressure is 50 to 100 MPa; Preferably, the pressure in the isostatic pressing treatment is 150-300 MPa; Preferably, the sintering treatment is performed at a temperature of 1000-1100°C and for a time of 3-8 hours; more preferably, heat treatment is performed after the sintering treatment, and the heat treatment includes a first-stage heat treatment and a second-stage heat treatment performed in sequence, wherein the first-stage heat treatment is performed at a temperature of 800-900°C and for a time of 1-3 hours; wherein the second-stage heat treatment is performed at a temperature of 400-600°C and for a time of 2-8 hours.

10. The method for preparing NdFeB according to any one of claims 1 to 9, characterized in that: The NdFeB sheet is obtained by melting and casting from a heavy rare earth-free N40H formula, and has a thickness of 0.2-0.4 mm.

11. NdFeB prepared by the method for preparing NdFeB according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Rapid forming method of high-performance Nd-Fe-B magnetic body

    CN103632835A

  • A neodymium-iron-boron magnetic material for a new energy source steam drive motor and a preparation method thereof

    CN109065315A

  • Method and equipment for laser cladding of heavy rare earth wire on surface of neodymium iron boron

    CN112635188A